ANALYSIS OF THE COMPOSITION OF THE STANDARD OF LIVING AND INCOME OF THE POPULATION - Khojiev Jakhongir Dushabaevich (International Journal of Innovations in Engineering Research and Technology, 2023)
This article examines the importance of statistical study of population living standards disparities. A system of statistical indicators representing the standard of living of the population has been studied and statistically analyzed. The standard of living of the population of our republic and the factors affecting its increase are statistically evaluated and scientific and theoretical recommendations are given.